Kinetic and kinematic comparison of alpine ski racing disciplines as a base for specific conditioning regimes - Kröll, J.; Spörri, J.; Kandler, C.; Fasel, B.; Müller, E.; Schwameder, H. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this preliminary case study was to compare the alpine ski racing competition disciplines slalom and giant-slalom with respect to principal kinematics of the lower limbs and the acting forces. Knee angles and ground reaction forces of one high level athlete were determined using inertial sensors and pressure insoles, respectively. Slalom was characterized by a "high dynamic skiing mode" with a distinct "knee angle and loading synchronism" between the inside leg and the outside leg. For giant slalom, a polarized situation was observed: "higher quasi static loads at high knee angles" on the outside leg and "lower eccentric-concentric loads at low knee angles" on the inside leg. These findings may help to increase the specificity of conditioning training and developing more discipline-specific exercises.